ATP Synthase K+- and H+-Fluxes Drive ATP Synthesis and Enable Mitochondrial K+-"Uniporter" Function: I. Characterization of Ion Fluxes. Issue 2 (13th December 2021) - Juhaszova, Magdalena; Kobrinsky, Evgeny; Zorov, Dmitry B; Nuss, H Bradley; Yaniv, Yael; Fishbein, Kenneth W; de Cabo, Rafael; Montoliu, Lluis; Gabelli, Sandra B; Aon, Miguel A; Cortassa, Sonia; Sollott, Steven J
Abstract: ATP synthase (F1 Fo ) synthesizes daily our body's weight in ATP, whose production-rate can be transiently increased several-fold to meet changes in energy utilization. Using purified mammalian F1 Fo -reconstituted proteoliposomes and isolated mitochondria, we show F1 Fo can utilize both ΔΨm -driven H + - and K + -transport to synthesize ATP under physiological pH = 7.2 and K + = 140 mEq/L conditions. Purely K + -driven ATP synthesis from single F1 Fo molecules measured by bioluminescence photon detection could be directly demonstrated along with simultaneous measurements of unitary K + currents by voltage clamp, both blocked by specific Fo inhibitors. In the presence of K +, compared to osmotically-matched conditions in which this cation is absent, isolated mitochondria display 3.5-fold higher rates of ATP synthesis, at the expense of 2.6-fold higher rates of oxygen consumption, these fluxes being driven by a 2.7:1 K + : H + stoichiometry. The excellent agreement between the functional data obtained from purified F1 Fo single molecule experiments and ATP synthase studied in the intact mitochondrion under unaltered OxPhos coupling by K + presence, is entirely consistent with K + transport through the ATP synthase driving the observed increase in ATP synthesis. Thus, both K + (harnessing ΔΨm ) and H + (harnessing its chemical potential energy, ΔμH ) drive ATP generation during normal physiology. Graphical Abstract: